LEARNING MOTIVATION IN IMPROVING STUDENTS' LEARNING OUTCOMES AT STATE SENIOR HIGH SCHOOL 4 GORONTALO - Buruji, Yuliyanti; Mondong, Tonny Iskandar; Malae, Andris K (CV. Fahr Publishing, 2025)
This study aims to examine students’ learning motivation in history subjects at SMA Negeri 4 Gorontalo and to identify the factors influencing that motivation. The research adopts a qualitative method with a descriptive approach. Data were collected through classroom observations, in-depth interviews with thirteen respondents—including three history teachers and ten students—and document analysis involving students’ learning outcomes such as assignment books, daily test scores, and report card grades. The findings reveal a noticeable decline in students’ academic performance at SMA Negeri 4 Gorontalo, primarily due to the implementation of a dual-shift learning system following a school fire incident. Shortened instructional time, an unconducive learning environment, and decreased student interest and motivation have led many students to struggle with understanding the material, neglect assignments, and ultimately obtain low scores. These results underscore the significant influence of learning environment conditions on both student motivation and academic achievement. Furthermore, the study offers new insights into how emergency conditions—particularly the implementation of a dual-shift system in post-disaster settings—can affect student motivation and performance in history education. This research is particularly important given the limited existing literature on educational challenges in disaster-affected schools, especially within the Indonesian context.